The Politics and International Relations of Fantasy Films and Television - Campbell, Joel R. author. aut Link
IX, 274 p. 1 illus.
Keywords: “This is a masterful examination of fantasy films and television series, and the ways that they illustrate political themes. The book effectively employs constructivist theory to show how fantasy franchise norms, values, and institutions have changed over time. Looking in detail at Game of Thrones, Lord of the Rings, the Harry Potter movies, along with fairytales and children’s tales, readers gain a sense of the usefulness of these stories as vehicles for understanding politics. They also come to appreciate these movies and TV shows as allegories of contemporary politics and international relations.” —Hieyeon Keum, University of Seoul, South Korea “Fantasy movies create…a broad canvas on which authors and filmmakers weave amazing yarns that express our fondest hopes and greatest fears. This book is one of the best studies of fantasy films and television and their expression of political ideas. I was particularly struck by the author’s illustration of the changing roles of women and girls in many of these stories, as female empowerment recently has become a major theme of fantasy projects. You can learn much about both fantasy stories and politics. Buy this book.” —Barry Pollick, Okinawa University, Japan This book uses several fantasy movies or movie series and television series to explain political and international relations (IR) concepts and theories. It indicates the importance of fantasy in literature, film and television, and its increasing impact on politics and International Relations. It then presents the political, IR, and social issues in each franchise, and in five chapters uses these tales’ key story arcs or plot points to illustrate major political and IR themes. The volume pays particular attention to such fantasy franchises as Lord of the Rings, Game of Thrones, the Harry Potter films, recent fairytale and children’s stories, and female-led fantasy projects. Joel R. Campbell is Associate Professor of political science at Troy University. He teaches in the Masters of Science in International Relations (MSIR) program in Troy's Pacific Region (Japan and Korea).